Synthesis of dialkylaminoaryl phosphonate bioisosteres of tyrosine and tyramine: a novel application of allene phosphonate chemistry for the synthesis of false substrates of tyrosinase - Dean Mazzuca, Christo Angelov, Leonard I Wiebe (Journal of Applied Pharmaceutical Science, 2015)
Tyrosinase is the rate-limiting oxidase in the synthesis of melanin, making it an obvious target for the treatment of melanotic melanomas. Tyrosine and tyramine are its natural substrates, but many of their derivatives are inhibitors or false substrates, and are therefore prime candidates for melanoma chemotherapy. A series of dialkylphosphonate derivatives of tyramine have now been synthesized in order to extend the chemical diversity of tyrosinase substrates. The known reactivity between alkenephosphonates and nucleophiles was exploited by the addition of 4-(2-aminoethyl)phenol (tyramine) across the 2,3-double bond of 1,2-alkadiene phosphonates, to obtain the desired bisphosphonate derivatives. These reactions were highly chemoselective and regioselective but not stereoselective. Five of the reported novel dialkylphosphonate aminophenols were substrates for mushroom tyrosinase in vitro: dimethyl 2-[2(4-hydroxyphenyl)ethylamino]-3-methyl-1-butenephosphonate (3);diethyl 2-[2(4-hydroxyphenyl)ethylamino]-3-methyl-1-butenephosphonate (4);dimethyl 2-[2-(4-hydroxyphenyl)ethylamino]-2-cyclohexyl-1-ethenephosphonate (5);diethyl 2-[2-(4-hydroxyphenyl)ethylamino]-2-cyclohexyl-1-ethenephosphonate (6);diethyl 2-[2-(4-hydroxyphenyl)ethylamino]ethanephosphonate (7). Compound 3 blocked the pigmentation of anagen hair in vivo in a murine animal model, a further demonstration that these compounds are able to enter and disrupt the melanogenic pathway.
Keywords: 1,2-Alkadienephosphonates, aminophenols, melanoma, tyramine, tyrosinase, melanin, melanogenesis, anagen hair pigmentation.